Timing of cholecystectomy in mild gallstone pancreatitis: a single centre study over 10-year period - Kim, Yegi S.; Vanguardia, Maria K.; Pilgrim, Charles; Giblin, Rachel; Selvaraj, Priyadarshini; Wijesinghe, Nuhansi (International Surgery Journal, 2025)
Background: The recommended management of mild gallstone pancreatitis (GSP) is to perform index admission cholecystectomy. This study is to assess the timing of cholecystectomy in patients presented with mild GSP in a single centre, over 10-year period, and assess the rates of complications in different timings of the surgery. Methods: Patients diagnosed with gallstone pancreatitis between 2009 and 2022 in Peninsula Health were identified using a diagnosis coding system. Results: A total of 198 patients were diagnosed with mild GSP between 2009 and 2022. 24 (12%) patients underwent early cholecystectomy (within 48 hours of admission), 106 (54%) underwent delayed cholecystectomy (over 48 hours) and 68 (34%) underwent interval cholecystectomy. The average length of hospital stay (LOS) was lower in patients who had early cholecystectomy (3 days) than patients who had delayed (6 days) or interval cholecystectomy (8 days). The complication rates were higher in patients who were in delayed cholecystectomy group (14%) or in interval cholecystectomy group (26.5%) than patients who underwent early cholecystectomy (4%) which was statistically significant (p=0.024). Conclusions: The gold standard management of mild GSP is to perform cholecystectomy at index admission. This study showed that the patients who underwent cholecystectomy within 48 hours of admission had no increased rate of perioperative complication and significantly reduced LOS.